2021
DOI: 10.1158/1541-7786.mcr-20-1022
|View full text |Cite
|
Sign up to set email alerts
|

RAF-Mutant Melanomas Differentially Depend on ERK2 Over ERK1 to Support Aberrant MAPK Pathway Activation and Cell Proliferation

Abstract: Half of advanced human melanomas are driven by mutant BRAF and dependent on MAPK signaling. Interestingly, the results of three independent genetic screens highlight a dependency of BRAF-mutant melanoma cell lines on BRAF and ERK2, but not ERK1. ERK2 is expressed higher in melanoma compared with other cancer types and higher than ERK1 within melanoma. However, ERK1 and ERK2 are similarly required in primary human melanocytes transformed with mutant BRAF and are expressed at a similar, lower amount compared wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…For example, our results indicate that, for SH-SY5Y and HCT-116 cells, ulixertinib exhibits less excessive toxicity than SCH772984, which is supported by KinomeScan data that show less off-targets for ulixertinib ( 49 ) than for SCH772984 ( 38 ). Also, it was recently suggested that BRAF mutant cancer cells are dependent on ERK2, but not ERK1 ( 50 ), so selective targeting of ERK2 rather than both kinases may reduce the toxicity of ERK1/2 inhibitors. Ulixertinib and ravoxertinib, which showed lower toxicity than other drugs, have a higher affinity toward ERK2 than ERK1 ( 28 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, our results indicate that, for SH-SY5Y and HCT-116 cells, ulixertinib exhibits less excessive toxicity than SCH772984, which is supported by KinomeScan data that show less off-targets for ulixertinib ( 49 ) than for SCH772984 ( 38 ). Also, it was recently suggested that BRAF mutant cancer cells are dependent on ERK2, but not ERK1 ( 50 ), so selective targeting of ERK2 rather than both kinases may reduce the toxicity of ERK1/2 inhibitors. Ulixertinib and ravoxertinib, which showed lower toxicity than other drugs, have a higher affinity toward ERK2 than ERK1 ( 28 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main proteins translated by the ERK1 and ERK2 genes are the 44 and 42 kDa isoforms, respectively. These isoforms usually share similar characteristics, although some differences between them do exist under restricted conditions or in specific cell types [ 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 ]. Aside from these main isoforms, initial studies reported the existence of additional, slightly different transcripts called ERK1psi [ 118 ] and ERK2a [ 119 ]; however, these transcripts exist only on the RNA level and are not translated into a stable protein.…”
Section: The Mek1b-erk1c Axismentioning
confidence: 99%